2018
DOI: 10.12681/mms.14158
|View full text |Cite
|
Sign up to set email alerts
|

Temperature regulates the switch between light-synchronized and unsynchronized activity patterns in the subtidal bivalve Pinna nobilis

Abstract: The present study reports new knowledge into the biological rhythms of subtidal bivalves using the fan mussel Pinna nobilis as model. The objective was determining which factor(s) provoke the change between two different patterns observed in the annual cycle of this species: P1, characterized by the individuals opening and closing their valves following the presence and absence of ambient light and P2, characterised by a behaviour independent of the presence of light. Magnetoresistive sensors were installed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Therefore, recently transplanted individuals need time to attach to the bottom, which makes them more vulnerable to drag forces or predators. Hence, a natural attachment to hold them, anti-predator cages, or an artificial extension of the byssus to fix the individuals to the seabed (Hernandis et al, 2018), appears to be necessary to maximize survival.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, recently transplanted individuals need time to attach to the bottom, which makes them more vulnerable to drag forces or predators. Hence, a natural attachment to hold them, anti-predator cages, or an artificial extension of the byssus to fix the individuals to the seabed (Hernandis et al, 2018), appears to be necessary to maximize survival.…”
Section: Discussionmentioning
confidence: 99%
“…P. nobilis can be cited to be a summer breeder species according to the classification by Boolotian et al (1962) considering spawning in terms of comparison of spawning periods (Table 1). These differences may occur due to depth, thermocline position, degrees of latitudes and other regionals (Hernandis et al, 2018). As for the collection of sexually mature individuals, it is necessary to choose periods when condition index is high and muscle index low (Acarli et al, 2015;Angel-Dapa et al, 2015;Acarli et al, 2018).…”
Section: Reproduction and Maturationmentioning
confidence: 99%
“…Besides the direct response to natural or anthropogenic stressors, several studies monitoring gaping behaviors over time, have shown cyclical patterns at different time scales, linked to extrinsic factors [ 22 24 ]. Circadian rhythms (periodicity cycle “τ” = 24.0h) in valve gaping, with a clear opening difference between day and night, have been reported for many bivalves, including freshwater and marine species, in various environments from temperate to tropical to Arctic waters.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were supplemented by Hernandis Caballero et al . [ 24 ] showing that temperature regulates the switch between these seasonal trends. Oyster gaping activity seems driven by a complex association of solar and lunar cycles, exhibiting circadian and seasonal rhythms with nocturnal activity in autumn–winter and diurnal activity in spring–summer [ 22 , 36 ].…”
Section: Introductionmentioning
confidence: 99%